Mussel‐Inspired Dendritic Polymers as Universal Multifunctional Coatings1. Issue 43 (8th September 2014) - Wei, Qiang; Achazi, Katharina; Liebe, Hendrik; Schulz, Andrea; Noeske, Paul‐Ludwig Michael; Grunwald, Ingo; Haag, Rainer
Abstract A rapid and universal approach for multifunctional material coatings was developed based on a mussel‐inspired dendritic polymer. This new kind of polymer mimics not only the functional groups of mussel foot proteins (mfps) but also their molecular weight and molecular structure. The large number of catechol and amine groups set the basis for heteromultivalent anchoring and crosslinking. The molecular weight reaches 10 kDa, which is similar to the most adhesive mussel foot protein mfp‐5. Also, the dendritic structure exposes its functional groups on the surface like the folded proteins. As a result, a very stable coating can be prepared on virtually any type of material surface within 10 min by a simple dip‐coating method, which is as fast as the formation of mussel byssal threads in nature.